Teachers’ Role in Guiding Students’ Digital Literacy on Social Media Use - Atha Nadia; Khusnul Isma Nuriza (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
The use of social media among elementary school students is no longer limited to communication, but has also become part of their daily entertainment and interaction. This study discusses how teachers at SDIT Nurul Hikmah Sidoarjo guide students in understanding digital literacy, especially in relation to TikTok, WhatsApp, and Roblox as a digital gaming platform with social interaction features. The research used a descriptive qualitative approach through observation, interviews, and documentation. The participants were 60 students from grade II and grade VI, along with four teachers who were actively involved in classroom learning and school digital activities. Field data showed that all students were familiar with the three platforms. In grade II, 17 students already used their own mobile phones, while in grade VI the number reached 23 students. Most students accessed digital media after school, during free time, or on holidays. Teacher guidance was carried out through classroom reminders, discussion of digital ethics, Islamic values, technology-based projects, and communication with parents. Several problems also appeared, such as reduced concentration, imitation of TikTok expressions, frequent talks about online games, and limited social interaction among some students. These findings show that digital literacy in elementary school needs continuous guidance from both teachers and parents.